The Multilevel Effects of Changes in Disadvantage on Changes in Crime - Wenger, Marin R. (Crime & delinquency, 2023)
While social disorganization theory suggests the importance of change, most prior research examining macro-level criminological associations uses cross-sectional data. The current study examines the multilevel relationship between changes in disadvantage and changes in crime over time using four data sources: the National Neighborhood Crime Study, the 2000 U.S. Census, crime-incidents occurring between 2005 and 2009, and the 2005?2009 American Community Survey. Analyzing 6,068 census tracts within 53 large U.S. cities using multilevel models with time nested within tracts nested within cities, I parse out the contribution of changes in tract-level disadvantage from city-level disadvantage to changes in robbery and burglary rates. Results indicate the importance of both static and dynamic associations between disadvantage and crime, at both the neighborhood and city level.